O imposto sobre serviços de qualquer natureza e os conflitos de competência tributária - Rocha, João Gabriel Laprovitera (2012)
The present dissertation focuses on the study of the causes and mechanisms for the prevention and solution of (apparent) conflicts of taxing power over Tax Services of any kind - ISS, which charge was constitutionally assigned to Municipalities. Therefore, it starts from the rescue of the very concept of State and the analysis of its federative form of politicaladministrative organization, comparing the model adopted by different countries. It emphasizes the Brazilian federative experience, highlighting the important issue of autonomy granted by the 1988 Federal Constitution to local government entities, especially in the tax and financial aspects. It also studies, though occasionally, the phenomenon of war tax, pointing its causes, consequences and alleged solutions. It enters specifically in the field of taxing power standards set by the 1988 Federal Constitution, which outlines each tax limits of incidence. Then the appropriate interpretative methods are studied, in order to extract the correct definition and scope of the concepts which appear in the text of the constitutional rules, fixing at the end some premises that will be extremely valuable to prevent or resolve any impasse regarding to the taxing power. Further, it promotes a study into the constitutional framework of ISS in order to scrutinize all the nuances of such tax and absorb the true meaning of signs present in its basic rule of incidence. Finally, it faces the more practical tortuous cases, related to conflicts of jurisdiction between the Municipality and Union,Municipality and State, and between the Municipalities themselves. Therefore, the author intends to contribute to lessen the possibility of disputes between federal agencies regarding to the exercise of their respective taxing powers granted by the Federal Constitution.